Across America on an emigrant train - Murphy, Jim, 1947- (New York : Clarion Books, 1993)
Combines an account of Robert Louis Stevenson's experiences as he traveled from New York to California by train in 1879 and a description of the building and operation of railroads in nineteenth-century America.
Includes bibliographical references (p.[139]-144) and index.
1180
Accelerated Reader AR
Keywords: Stevenson, Robert Louis, -- 1850-1894 -- Travel -- United States -- Juvenile literature; Stevenson, Robert Louis, 1850-1894.; Railroad travel -- United States -- History, -- 19th century; Authors, Scottish, 19th century -- Biography -- Juvenile literature; Railroads -- History; United States -- Description and travel, 1865-1900 -- Juvenile literature; United States -- Description and travel